Computational collective intelligence. 8th International Conference, ICCCI 2016, Halkidiki, Greece, September 28-30, 2016. Proceedings /: 8th International Conference, ICCCI 2016, Halkidiki, Greece, September 28-30, 2016. Proceedings. Part II : (2016) - Unknown
No abstract available